(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: (i) To assess the situation of myopia in schools of students at Thanh Liet secondary school, Thanh Tri, Hanoi in 2022; (ii) Analysis of some factors related to the current situation of school myopia of the study subjects. Subjects - Methods: Students from grades 6 to 9, conduct a simple random sampling: select 3 classes/block by lottery and select all students of classes participating in the study including 420 students. Methods: A cross-sectional description with analysis and use of secondary data. Result: As a result, there were 420 students participating in the study, accounting for 55.5% of myopia. In which, 57.5% of students with myopia do not wear glasses. The average age at being diagnosed with myopia among students participating in the study was 9.0 (±2.6). Female students are 1.5 times more likely to have myopia than male students (95% CI: 1.0 - 2.3; p<0.005). Students with a family member with myopia are 2.2 times more likely to have myopia than students without a family member with myopia (95% CI: 1.4 – 3.2; p< 0.001); Students who do not have a home study corner are 3.7 times more likely to have myopia than those with a home study corner (95% CI: 2.2 – 6.4; p<0.001). Students using non-standard desks and chairs for home study are 3.0 times more likely to have myopia than those using standard desks and chairs (95%CI: 1.8 – 5.0; p< 0.001). Conclude: The study has given two main goals to discuss, firstly, about the situation of myopia in secondary school students in Thanh Liet, Thanh Tri, Hanoi in 2022, with the rate of myopia being 55.5%. 233 students) and 42.5% of myopia students wore glasses. The average age of being diagnosed with myopia in students participating in the study was 9.0 (±2.6); Secondly, on some factors related to the situation of school myopia, the study found the relationship of a number of factors with the situation of school myopia in students, including Gender factors: Females are likely to Myopia is 1.5 times higher than that of men; family factors: students with a family member with myopia are 2.2 times more likely to have myopia than students without a family member with myopia; The learning factors related to the classroom teaching are: “Home study corner”, “type of light”, “type of desk and chair for home study”. Vietnam Journal of Community Medicine, Vol 64, No 3 (2023) 134-141 INSTITUTE OF COMMUNITY HEALTH *Corressponding auth